(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The purpose of this Study to investigate the difficulties faced by secondary SchoolStudents when attempt to learn mathematics. Personal problems, Emotional problems, languageproblems, Problems on teacher’s instruction, Problems with school facilities and infrastructure, andProblems arising from excessive workloads and extracurricular activities in schools are the categoriesthat are used to classify the challenges and obstacles. For the purpose of the study, 250 students werechosen at random. For the purpose of collecting data, a self-administered open-ended questionnaire wasutilised.During the design of the study, it was discovered that there are a number of problems that areassociated with the method of teaching and learning mathematics, and these problems require that theybe remedied in an appropriate manner. Students are often discouraged from studying mathematicsbecause they do not have sufficient motivation to do so. They were instructed in mathematics from theperspective of the examination. As a result, a smaller number of students are willing to continuestudying mathematics in higher education.